PENGARUH PENGEMBANGAN SDM, GAYA KEPEMIMPINAN DAN TEKNOLOGI TERHADAP EFEKTIVITAS KERJA PEGAWAI DI PUSKESMAS MENINTING - Syatriawan Perdana Putra (Nusantara Hasana Journal, 2024)
The main objective of this research is to analyze the influence of Human Resources (HR) development, leadership style, and technology on the work effectiveness of employees at the Meninting Community Health Center (Puskesmas). This research uses quantitative methods with an associative (causal) approach to evaluate the relationship and influence of these variables on employee work effectiveness. The results of multiple linear regression analysis show that the three variables studied, namely human resource development, leadership style and technology, have a significant influence on the work effectiveness of employees at the Meninting Community Health Center. Human resource development, through training, education and relevant work experience, has a positive impact on employee work effectiveness. An instructional leadership style that includes direction, guidance, knowledge, motivation and support from the head of the Community Health Center also makes a positive contribution to employee work effectiveness. In addition, the use of information technology, such as health information systems, has a significant influence on the work effectiveness of employees at the Meninting Community Health Center. In order to increase employee work effectiveness, this research recommends the importance of developing human resources through training and developing employee skills, implementing an instructional leadership style that provides direction and support, and using appropriate information technology. By paying attention to these factors, the Meninting Community Health Center can effectively improve the quality of health services to the community.